2008
DOI: 10.1029/2007wr006132
|View full text |Cite
|
Sign up to set email alerts
|

Temporal evolution of low‐flow regimes in Canadian rivers

Abstract: [1] This study investigates temporal evolution of 1-, 7-, 15-, and 30-day annual and seasonal low-flow regimes of pristine river basins, included in the Canadian reference hydrometric basin network (RHBN), for three time frames : 1974-2003, 1964-2003, and 1954-2003. For the analysis, the RHBN stations are classified into three categories, which correspond to stations where annual low flows occur in winter only, summer only, and both summer and winter seasons, respectively. Unlike in previous studies for the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 57 publications
10
88
0
1
Order By: Relevance
“…an independent and identically distributed (IID) random variable or an autoregressive (AR) process have been questioned (Cohn and Lins, 2005;Koutsoyiannis and Montanari, 2007). Several studies have shown that streamflow does not behave as an IID or AR process, but tends to exhibit long-term persistence (LTP) and variability (e.g., von Storch, 1995;Koutsoyiannis, 2003Koutsoyiannis, , 2006Khaliq et al, 2008;Chen and Grasby, 2009). In addition, there are concerns about the power of various tests in the presence of auto and cross-correlation (Yue and Wang, 2002;Hamed and Rao, 1998).…”
Section: Trend Magnitudementioning
confidence: 99%
“…an independent and identically distributed (IID) random variable or an autoregressive (AR) process have been questioned (Cohn and Lins, 2005;Koutsoyiannis and Montanari, 2007). Several studies have shown that streamflow does not behave as an IID or AR process, but tends to exhibit long-term persistence (LTP) and variability (e.g., von Storch, 1995;Koutsoyiannis, 2003Koutsoyiannis, , 2006Khaliq et al, 2008;Chen and Grasby, 2009). In addition, there are concerns about the power of various tests in the presence of auto and cross-correlation (Yue and Wang, 2002;Hamed and Rao, 1998).…”
Section: Trend Magnitudementioning
confidence: 99%
“…Zhang et al 2001, Burn and Hag Elnur 2002, Yue et al 2001, Cunderlik and Burn 2004, Hodgkins and Dudley 2006, Khaliq et al 2008, Ehsanzadeh and Adamowski 2009, Burn et al 2010. The trend analysis studies have differed in: the variables examined, the approach used to identify trends, and the scope of the analysis, some studies being national in scope, while others have examined specific regions of Canada.…”
Section: Canadian Reference Networkmentioning
confidence: 99%
“…Lettenmaier et al, 1994;Rose, 1. Introduction 2009;Lins and Slack , 1999;Small et al, 2006;Regonda et al, 2005;Khaliq et al, 2008].…”
Section: Trendsmentioning
confidence: 99%